Correcting misperceptions about ethno-racial discrimination: The limits of evidence-based awareness raising to promote support for equal-treatment policies - Merlin Schaeffer; Krzysztof Krakowski; Asmus Leth Olsen (American Journal of Political Science, 2024)
The disadvantages experienced by minorities and lack of societal remedies are partly attributable to native-majority citizens' limited awareness of minority hardships. We investigate whether informing citizens about field-experimental audits on ethno-racial discrimination increases their recognition of the issue and support for equal-treatment policies. Extending a largely US-centric research frontier, we focus on beliefs about discrimination faced by Muslims in Denmark. To further comprehension, we test three types of framing: a scientist stressing credibility, a lawyer emphasizing the legal breach, or a minority expressing grief. Our survey experiment ( n ~=~4,800) shows that citizens are generally aware of discrimination and tend to overperceive its extent. Communicating audit evidence corrects misperceptions but does not change recognition or policy support, regardless of framing or initial misperception. Only combining priming, correction, and framing temporarily increases recognition and donations to support groups. These findings suggest that audit-based awareness campaigns have limited immediate success beyond donations acknowledging minority hardships.
https://doi.org/10.7910/DVN/HRUXYI
Keywords: 320